Analysis of Nano-Wires at Terahertz and Optical Frequencies Using Surface Impedance Models - Alireza Gholipour (AUT Journal of Electrical Engineering, 2021)
Different surface impedance models are applied to circular nano-wires at terahertz and optical frequencies and the accuracy of these surface impedance boundary conditions (SIBCs) is studied. The simplest form of SIBC defines a local relation between the tangential electric and magnetic equivalent surface currents at each point on the boundary. This definition is very dependent on the constituent material of the wire and its radius. The generalized IBC (GIBC) improves the accuracy of the local definition by considering the curvature of the surface at each observation point. On the other hand, the operator definition of the surface impedance presented in the SIGO method (surface impedance generating operator), is an exact field theoretical approach that determines the relation between equivalent electric and magnetic surface currents. Moreover, this method is suitable for parallel processing. For the special case of circular wires, the SIGO operator is derived. To validate the SIBC models, the results are compared with the SIGO. In spite of its extreme simplicity, it is observed that the accuracy of SIBC models is limited at optical and terahertz frequencies. It is also shown that some forms of SIBCs presented in the literature for nano-wires can be considered as special cases of SIGO formulation.